2007
DOI: 10.1093/carcin/bgm162
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the mechanism by which increased spermidine/spermine N1-acetyltransferase activity increases susceptibility to skin carcinogenesis

Abstract: Previous studies have shown that keratin 6 (K6)-spermidine/spermine N1-acetyltransferase (SSAT) transgenic mice, which modestly over-express SSAT in the skin, are more sensitive to tumor induction by a two-stage tumorigenesis protocol using initiation with 7,12-dimethylbenz[a]anthracene (DMBA) and promotion with 12-O-tetradecanoylphorbol-13-acetate (TPA). To evaluate the role of altered levels of polyamines and oxidative stress in this increase, studies were carried out with pharmacologic and genetic manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
3
33
0
Order By: Relevance
“…Thus, although acetyl-CoA depletion appears to be involved in the former, alternative metabolic disturbances are likely to be responsible for the latter. Similarly, a recent study found that selective SSAT expression in mouse skin increased sensitivity to chemical carcinogens due to elevations in ODC activity and Put levels, both indicative of increased flux with increased liberation of toxic metabolic by-products (59).…”
Section: Discussionmentioning
confidence: 83%
“…Thus, although acetyl-CoA depletion appears to be involved in the former, alternative metabolic disturbances are likely to be responsible for the latter. Similarly, a recent study found that selective SSAT expression in mouse skin increased sensitivity to chemical carcinogens due to elevations in ODC activity and Put levels, both indicative of increased flux with increased liberation of toxic metabolic by-products (59).…”
Section: Discussionmentioning
confidence: 83%
“…37 Conversely, expression of another polyamine catabolic enzyme SSAT under the keratinocyte-specific K6 promoter was shown to promote skin tumors. 38 Interestingly, treatment of these mice with MDL72527 partially counteracted tumor growth, 38 indicating that inhibition of polyamine catabolism can be a potential therapeutic tool to suppress tumor formation. It is noteworthy that enhanced polyamine synthesis has also been shown to promote tumor growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that enhanced polyamine synthesis has also been shown to promote tumor growth and progression. 38 For example, overexpression of the polyamine biosynthesis enzymes ODC or SAMDC induced malignant transformation. 38,39 All these observations together suggest that disruption of the homeostatic balance of polyamine ratios and not their overall cellular increase could support tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different cells and tissues, the TGF-β signaling pathway plays different roles [21,22] : it stimulates cell division in fibroblasts but inhibits growth in epithelial cells; it also weakens the cell adhesion effect through inducing the tyrosine phosphorylation of β-catenin, Previous data have shown that SAT is predominantly localized to mitochondria [27] . SAT overexpression is correlated with tumorigenesis [28] . The basic structural unit of the nucleosome is an octamer of four core histones, H2A, H2B, H3, and H4, around which a 146-bp fragment of DNA is wrapped [29] .…”
Section: Pcbp1 Sat H2afx Fos Fst Tp53 Map2k2 Andmentioning
confidence: 99%